Contrasting Patterns of Climatic Niche Divergence in Trebouxia—A Clade of Lichen-Forming Algae - Nelsen, Matthew P.; Leavitt, Steven D.; Heller, Kathleen; Muggia, Lucia; Lumbsch, H. Thorsten (Frontiers in Microbiology, 2022)
Lichen associations are overwhelmingly supported by carbon produced by photosynthetic algal symbionts. These algae have diversified to occupy nearly all climates and continents; however, we have a limited understanding of how their climatic niches have evolved through time. Here we extend previous work and ask whether phylogenetic signal in, and the evolution of, climatic niche, varies across climatic variables, phylogenetic scales, and among algal lineages in Trebouxia—the most common genus of lichen-forming algae. Our analyses reveal heterogeneous levels of phylogenetic signal across variables, and that contrasting models of evolution underlie the evolution of climatic niche divergence. Together these analyses demonstrate the variable processes responsible for shaping climatic tolerance in Trebouxia, and provide a framework within which to better understand potential responses to climate change-associated perturbations. Such predictions reveal a disturbing trend in which the pace at which modern climate change is proceeding will vastly exceed the rate at which Trebouxia climatic niches have previously evolved.